1987
DOI: 10.1097/00000658-198712000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cefazolin, Cefamandole, and Gentamicin as Prophylactic Agents in Cardiac Surgery

Abstract: In an effort to develop an improved regimen of antibiotic prophylaxis in cardiac surgery, 1030 patients who were to have elective cardiothoracic surgery involving a median sternotomy were selected at random to receive cefamandole or cefazolin, with or without gentamicin, in a prospective double-blind study. Cefazolin was significantly less effective than cefamandole at both the sternal (1.8% vs. 0.4%, respectively, p less than 0.05) and donor sites (1.3% vs. 0%, respectively, p less than 0.02). Seven Staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(33 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…There were no differences in the rates of postoperative wound infections. In the two larger studies, both cefamandole and cefuroxime clearly reduced the incidence of wound infections in comparison with cefazolin (14,28).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…There were no differences in the rates of postoperative wound infections. In the two larger studies, both cefamandole and cefuroxime clearly reduced the incidence of wound infections in comparison with cefazolin (14,28).…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, Gentry and colleagues (9) found no differences (14,28) in which wound infection pathogens were available, the microbiology of these postoperative infections indicated that, despite prophylaxis, staphylococci continued to produce infectious complications (Table 2). S. aureus and S. epidermidis accounted for more than one-half of the wound infections among cefazolin recipients.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…24 There is also no doubt that antibiotic prophylaxis is needed in selected "clean" surgical procedures where a prosthesis is implanted, because the consequences of a graft infection can be severe or even fatal. 25,26 Hip or knee arthroplasties 25 and cardiac or vascular graft implants 26 are "clean" procedures in which perioperative antibiotic coverage has been shown to be beneficial and is clearly indicated. However, the benefit of antibiotic prophylaxis in other "clean" surgical procedures, such as tension-free hernioplasty, has been considered questionable.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of clinical trials also suggest that P-lactamase activity may be clinically important. Although conflicting data have been reported (6), some studies of cephalosporins used as prophylaxis in cardiac surgery have indicated that either cefamandole (13,22) or cefuroxime (22) is more effective than cefazolin in prophylaxis of S. aureus wound infections. In addition, Kernodle et al (14) demonstrated that staphylococcal type A ,B-lactamase production is associated with a greater number of clean wound infections with cefazolin prophylaxis than with cefamandole prophylaxis.…”
mentioning
confidence: 99%